HUBUNGAN HARGA DIRI DENGAN PRESTASI BELAJAR MAHASISWA TAHUN KETIGA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Patriot Fajri Rakasiwi; Zulharman "; Firdaus " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTThe success can be evaluated through the achievement of learning that has been achieved in the study. Learning achievement is influenced by several factors, one of which is self-esteem. A person who has high self-esteem can easily identify yourself and can easily find out what he needed to improve learning achievement. The purpose of this study was to determine the correlation of self-esteem and academic achievement in 2011 Students of Medicine, University of Riau. This study used a cross sectional analytic method. The population is a student at the Faculty of Medicine, University of Riau in 2011 The sample was 115 students with a total sampling method. Researchers used a questionnaire based on the theory of Frey and Carlock about self-esteem and grade point average (GPA) to measure learning achievement. The statistical test for correlation adversity quotient and learning achievement using the Spearman correlation test. The results of this study have a correlation between self-esteem and achievement of learning with the strength and direction of a weak correlation (r = 0.2, p = 0.04). In conclusion there is a relationship between self-esteem and learning achievement in 2011 the Faculty of Medicine, University of Riau.Keywords: self-esteem, academic achievement, medical students